The Polity reader in gender studies. (Polity Press in association with Blackwell Publishers, 1994)
Gender studies has become one of the core fields in the social sciences and humanities. As a result of the struggles of feminists, women are no longer "hidden from history" or unacknowledged in social research or cultural analysis. Over recent years, again largely because of the influence of feminism, "masculinity" has also increasingly been made problematic and opened up to scrutiny. Gender is thereby recognised to be central to the analysis of structures of power, the organization of social and cultural institutions, and modes of ideological control in modern societies. This book provides an overview of the domain of gender studies. It covers the major theoretical debates about the nature of female and male identity, as well as offering a variety of analyses of gender in the context of different forms of social and cultural activity. Authors represented in the volume include the following: Seyla Benhabib, Rosi Braidotti, Nancy Chodorow, R. W. Connell, Catherine Hall, Michael Stanworth, Klaus Theweleit, Sylvia Walby and Jeffrey Weeks. The book is organized in such a way as to be accessible to beginning students. Each section in the volume is preceeded by a summary and description of the articles concerned.